The results of sociological research to improve the quality of pharmaceutical care - E A Mikhailova; N A Edigarova; A A Kuznetsov (RUDN Journal of Medicine, 2013)
Pharmaceutical assistance includes the procedure for consulting the doctor and the patient to determine the most efficient, safe and economically efficient course of treatment. With a view to improving the quality of pharmaceutical care, the authors carried out sociological research of medical and pharmaceutical staff.